Insights into the experiences of patients with cancer in London: framework analysis of free-text data from the National Cancer Patient Experience Survey 2012/2013 from the two London Integrated Cancer Systems. Issue 10 (19th October 2015) - Wiseman, Theresa; Lucas, Grace; Sangha, Amrit; Randolph, Anuska; Stapleton, Sarah; Pattison, Natalie; O'Gara, Geraldine; Harris, Katherine; Pritchard-Jones, Kathy; Dolan, Shelley
Abstract : Objective: To shed light on experiences of patients with cancer in London National Health Service (NHS) trusts that may not be fully captured in national survey data, to inform improvement action plans by these trusts. Design: Framework analysis of free-text data from 2012/2013 National Cancer Patient Experience Survey (NCPES) from the 2 London Integrated Cancer Systems. Setting and participants: Patients with a cancer diagnosis treated by the NHS across 27 trusts in London. Main outcome measures: Free-text data received from patients categorised into what patients found good about their cancer care and what could be improved. Methods: Using Framework analysis, a thematic framework was created for 15 403 comments from over 6500 patients. Themes were identified across the London data set, by tumour group and by trust. Results: Two-thirds of free-text comments from patients in London were positive and one-third of those related to the good quality of care those patients received. However, the majority of comments for improvement related to quality of care, with a focus on poor care, poor communication and waiting times in outpatient departments. Additionally, 577 patients (9% of those who returned free-text data in London) commented on issues pertaining to the questionnaire itself. Some patients who experienced care from multiple trusts were unclear on how to complete the questionnaire for the single trust whose care they were asked to comment on, others said the questions did not fit their experiences. Conclusions: NCPES free-text analysis can shed light on the experiences of patients that closed questions might not reveal. It further indicates that there are issues with the survey itself, in terms of ambiguities in the questionnaire and difficulties in identifying patients within specific trusts. Both of these issues have the potential to contribute to knowledge and understanding of the uses and limitations of free-text data in improving cancer services.